DIRECTIONS FOR IMPROVING CORPORATE GOVERNANCE IN MINING AND METALLURGICAL INDUSTRY ENTERPRISES (World Bulletin of Social Sciences, 2025)
Corporate governance is one of the main concepts of strategic importance for various organizations, especially large industrial enterprises. This system regulates relationships among shareholders, managers, and other stakeholders, ensuring transparency, stability, and efficiency in company operations. The corporate governance system is designed to protect shareholder interests, ensure transparency in business operations, and enhance social responsibility.